Membrane transport from the endoplasmic reticulum - Glick, Benjamin (Henry Stewart Talks, 2007)
Evolutionary origin of the ER, Role of the ER in membrane biogenesis, Export from the ER in COPII transport vesicles, Clustering of COPII components at transitional ER sites, Relationship between ER export and the Golgi apparatus, Cisternal maturation of Golgi compartments